Length–weight relationships of four fish species from Fatala estuary, Guinea, West Africa. (1st April 2022) - Sadio, Oumar; Simier, Monique; Le Loc'h, François; Tito de Morais, Luis
Abstract: This study provides length‐weight relationships (LWR) that had not yet been reported for four fish species belonging to four different families: Chrysichthys johnelsi Daget, 1959, Cynoglossus senegalensis (Kaup, 1858), Citharichthys stampflii (Steindachner, 1894) and Pseudotolithus typus, Bleeker, 1863. Data were collected in the Fatala estuary, republic of Guinea, each month between January 1993 and March 1994, using alternately a purse seine net (length 250 m, height 20 m, 14 mm side mesh) and gillnets (side mesh sizes of 10, 12.5, 15, 15.5, 20, 22.5, 25, 30, 35 and 40 mm). For each fish specimen, fork or total length and total weight were measured with precision to 0.1 cm and 0.1 g respectively. A wider size range, compared to the size range available in FishBase, was obtained for Pseudotolithus typus . The present study also provides a new maximum total length for Citharichthys stampflii . The determination coefficient ( r ²) between length and total body weight ranged between 0.958 in Citharichthys stampflii and 0.989 in Cynoglossus senegalensis . The allometric coefficient b varied from 2.9552 ( Chrysichthys johnelsi ) to 3.7288 ( Citharichthys stampflii ). The value of LWRs for the four fish species should assist fisheries scientists and managers to complement their further studies of population parameters to improve management decisions in Fatala estuary and, more widely, in West Africa.